Estimating the energy saving potential of residential consumption in China based on decent living standards - Yu, Yawen; Yang, Jin; Chai, Song; Tang, Lin (Frontiers in Environmental Science, 2022)
The basic well-being of residents should be fully considered when making residential energy-saving policies. In this study, decent living standards for China were proposed. The provincial energy saving potential of Chinese residents were estimated from a lifetime perspective using environmental extended input–output analysis. The results show that, in 2017, the energy saving potential of Chinese residents constituted 32.74% of total energy consumption. The consumption categories of transportation, housing and cooking had the greatest energy saving potential of 1668.40, 3540.83 and 3229.75 trillion kJ, respectively, in which direct energy consumption accounted for 85% of total energy consumption. For food, clothing, water, health care and education, there was only energy saving potential from indirect consumption, of which food has the largest indirect energy consumption of 3159.25 trillion kJ. Moreover, the energy saving potential varied at the provincial level, coming from different consumption categories. Special attentions should be paid to the transportation in Beijing, housing in Liaoning, and cooking in Gansu, which have relatively greater energy saving potential with per capita energy saving potential of 207.38, 1002.16, and 4256.6 thousand kJ, respectively. The results verify the importance of differentiated and targeted energy policies for residential consumption in different provinces.